A Rare Skin Lesion During Pregnancy: Localized Cutaneous Leishmaniasis - Çetin, Cihan; Büyükkurt, Selim; Köksal, Fatih; Özgünen, Tuncay (Gynecology Obstetrics & Reproductive Medicine, 2016)
Leishmaniasis is an infectious disease that is spread by phlebotomine sand flies. These flies cause infections called cutaneous and/or visceral leishmaniasis in humans. In this paper, we present a pregnant patient who was diagnosed with localized cutaneous leishmaniasis, a localized form of the disease, and the treatment we applied to the patient. The patient was given systemic amphotericin-B treatment, however the immunosuppressive state of pregnancy and the diabetes of the patient complicated the treatment. Although the size of the lesion regressed during pregnancy, we could not completely cure the disease.